The Differences between Emotional Freedom Technique (EFT) and Self-Hypnosis on Anxiety among Menopausal Women - Julia, A. A. Istri Diah Intan; Widiastini, Luh Putu; Sumawati, Ni Made Risna; Karuniadi, I Gusti Agung Manik (JURNAL KEBIDANAN, 2025)
The aging and menopausal process is considered to give a scary experience, especially in women, causing anxiety. This study aimed to identify the difference between Emotional Freedom Technique (EFT) and Self-Hypnosis into Anxiety level among Menopausal Women at the Klinik Pratama Osadha. This study employed the Quasy Experiment approach with a two-group pre-test-post-test design with a sample size of 40 people. The sample was then divided into two groups by 20 people each group and given the EFT and Self-Hypnosis as intervention. Both of the intervention was given once daily by 15 minutes and every day for the 7 days. The level of anxiety was assessed using the GAS (Geriatric Anxiety Scale) questionnaire and analyzed by the wilcoxon sign rank test and the mann whitney U test used to see the effect and test of the difference between the two groups. The results showed that there was a difference in anxiety levels before and after EFT intervention with a p-value of 0.000 < α 0.05 and before and after Self-Hypnosis intervention with a p-value of 0.001< α 0.05, and there was a significant difference between EFT and Self-Hypnosis interventions in reducing anxiety levels in menopausal women with a p-value of 0.000 < α 0.05, and the Z value was -3,549. This research is expected to be used as a reference source for education to develop evidence-based practice, especially regarding complementary therapies in an effort to reduce the level of anxiety in menopausal women.